Mononuclear cell subsets and coronary artery lesions in Kawasaki disease. Issue 6 (June 1992) - Furukawa, S; Matsubara, T; Yabuta, K
Abstract : The peripheral blood mononuclear cell subsets in patients with Kawasaki disease and coronary artery lesions were investigated. Of the 106 patients 14 had lesions. Patients with Kawasaki disease and coronary artery lesions were found to have increased counts of CD14+ macrophages/monocytes compared with those of patients with Kawasaki disease without lesions. The absolute counts of CD14+ macrophages/monocytes form an important parameter to determine the severity of vascular damage during acute Kawasaki disease.